A study on the perception, usage rate and satisfaction of herbal products among customers in the northern region./ Fatimah Mohd Saman…[et al.] - Mohd Saman, Fatimah; Ayob, Mohammad Zaki; Abdul Jalil, Muna (Research Management Institute, UiTM Kedah, 2003)
The use of herbs and herbal products has become widely accepted in our society, and this trend has benefited not only manufacturers and retailers, but also the consumers as well in terms of having varied choices. Herbal product sales have been very strong although the local content for these products is only 10%. Herbs such as tongkat ali (eurycoma longifolia), kacip fatimah (labisia pumila), pegaga (centella asiatica), serai wangi (cynbotogon nardus), and sena makki (cassia angustifolia) are well known and required in large quantities. This research is aimed at understanding evolving trends in the utilization of herbal products by the consuming public, especially those in Kedah, Penang, and Perlis. The main objectives of this research are (a) to understand customers’ perception of herbal products, (b) to find the consumption rate among herbal users, and (c) to measure the satisfaction level in consuming these products. The focus are on highly demanded categories such as Tongkat Ali (eurycoma longifolia) and Kacip Fatimah (labisia pumila) capsules, herbal coffee, pellets or “makjun”, toiletries, rubbing oils, balms, and slimming products. The research results indicate that variables such as price, packaging, efficacy, safety, natural ingredients, manufacturer’s reputation, do influence customer’s perception of herbal products, and understanding the variables will help the industry to position itself appropriately and develop effective marketing strategies